1995
DOI: 10.1530/eje.0.1320487
|View full text |Cite
|
Sign up to set email alerts
|

Formation of islet amyloid fibrils in beta-secretory granules of transgenic mice expressing human islet amyloid polypeptide/amylin

Abstract: To investigate the relationship between human islet amyloid polypeptide (IAPP)/amylin expression and islet amyloid deposits in the pathogenesis of human non-insulin-dependent diabetes mellitus (NIDDM), we developed transgenic mice using a human IAPP cDNA connected to an insulin promoter. Ribonucleic acid blotting and immunohistochemistry revealed the expression of the transgene in the pancreatic beta cells. Immunogold electron microscopy showed that beta-secretory granules contained the human C-terminal flanki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…5 A versus B). These were comparable to those described previously in a hemizygous transgenic mouse that did not develop diabetes mellitus (8). These intravesicular IAPP aggregates were not present in controls.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…5 A versus B). These were comparable to those described previously in a hemizygous transgenic mouse that did not develop diabetes mellitus (8). These intravesicular IAPP aggregates were not present in controls.…”
Section: Resultssupporting
confidence: 89%
“…However, similar intravesicular deposits are reported elsewhere in hemizygous h-IAPP transgenic mice that did not develop diabetes mellitus (8) and these deposits were not related temporally to cell death in the present study. It is therefore unlikely that these intravesicular aggregates of IAPP were responsible for 13-cell death in male transgenic mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Immunoreactivity for proIAPP fragments has been detected in some amyloid deposits [29] and it has been suggested that there is an increase in pro-IAPP intermediates in cultured human islets [30]; proIAPP fibrils either inside or outside the cells could act as an initiator for conversion of IAPP to beta conformation and fibril formation. The IAPPimmunoreactive material in beta-cell granules of TM has been described as fibrils [8,31]; if this represents some form of insoluble IAPP or proIAPP accumulation, this could act as a nidus for fibril formation [32] at the surface of the cell when the granule is released.…”
Section: Discussionmentioning
confidence: 99%
“…To study factors that may be important in islet amyloid formation, we and others have generated transgenic mice expressing human IAPP (hIAPP) in their islet ␤-cells (15)(16)(17)(18)(19). Islet amyloid deposition was observed in the vast majority of our hIAPP transgenic mice when maintained on a breeder chow (20) but not regular chow (17).…”
mentioning
confidence: 99%